Proyecto de factibilidad para la creación de una empresa de eventos sociales en la zona urbana de la ciudad de Loja - Novillo Tacuri, Jonathan Fabián (2015)
Aware and motivated by the need for the City of Loja Company expects quality social events, offering a comprehensive support lojana society, the proposed project is in the local context, particularly in the urban area Loja, and caters to families of the economically active population. The main objective of this work is to determine the feasibility of setting up business social events in the urban area of the city of Loja, and also determine the economic and social impact. It will provide a high quality service, drawing on the expertise of its employees, also have the special length as it relates to the realization and organization of social events. The study began with market research, where there is unmet demand for this type of service, 2666 families of the economically active population was identified. Market Research announced the acceptance of potential customers for this new company. Within the Technical Study conclusive analysis of factors for determining the location, production capacity, Manpower requirements, Raw Materials, Materials, Supplies and Equipment Technology that the company needs for beginning of its activity took place. As a result of the technical study it was obtained that "CACHE EVENTOS SOCIALES" is located in suburb May 24, in the streets May 24 and Lourdes, in the urban area of the city of Loja, will have rented facilities for customer public, with the aim of meeting 50% of the unmet 1333 families (5332 people) during the first year of operations. Similarly a flowchart in which the different processes and sub processes that must pass the client for the service recruitment identified was developed. The price to be offered in the new project will be based on the following categories.  Dish average price per person is 20 USD. In the first year of operations.  Average Marquees Rental price is 30 USD. The organization of the company is determined by its mission, vision, principles and values essential for the proper internal functioning of the firm pillars, plus professional profiles according to their role and responsibility was designed by Manual and Functions thus providing a quality service to the appropriate personnel. From Financial Investment Budget Survey was established value amounting to $ 48,551.38, the investment will be financed through its own resources by 42% ($ 20,551.38) and a loan from the Bank of Loja equivalent to 58% ( $ 28,000) of the total remaining investment. Revenue for the first year of the company's social events will be $ 87,112, generating a profit for its shareholders of $ 3,690.25. Breakeven points that must sell $ 81,338.76 and work with 94% in the first year in order to avoid losses. Cash Flow Project notes that the first year will be a liquidity of $ 4,436.83 and initial working capital of $ 5,928.38 is needed Financial evaluation indicators are all positive for the company, since the NPV is 32604.59, the IRR is 36.92%, and the cost benefit ratio indicates that for every dollar invested 0.18 cents utility will win, the recovery period is 6 years, 1 month and two days. The sensitivity analysis showed that income can be reduced to 7.2% and increase its costs by 8.32%. As a general conclusion the viability and feasibility of this project is determined, it is an investment that ensures the return of invested capital getting returns from the first year of operations at the start for the creation of the company is recommended "CACHÉ EVENTOS SOCIALES. The object is to provide customers with quality service and comprehensive and potencialice highlighting all relevant aspects of the service of social events